Coherent motions in a turbulent wake of an axisymmetric bluff body. (10th May 2023) - Zhang, Fengrui; Peet, Yulia T.
Abstract: Abstract : The wake flow past an axisymmetric body of revolution at a diameter-based Reynolds number $Re=u_{\infty }D/\nu =5000$ is investigated via a direct numerical simulation. The study is focused on identification of coherent vortical motions and the dominant frequencies in this flow. Three dominant coherent motions are identified in the wake: the vortex shedding motion with the frequency of $St=fD/u_{\infty }=0.27$, the bubble pumping motion with $St=0.02$, and the very-low-frequency (VLF) motion originated in the very near wake of the body with the frequency $St=0.002$ – $0.005$ . The vortex shedding pattern is demonstrated to follow a reflectional symmetry breaking mode, whereas the vortex loops are shed alternatingly from each side of the vortex shedding plane, but are subsequently twisted and tangled, giving the resulting wake structure a helical spiraling pattern. The bubble pumping motion is confined to the recirculation region and is a result of a Görtler instability. The VLF motion is related to a stochastic destabilisation of a steady symmetric mode in the near wake and manifests itself as a slow, precessional motion of the wake barycentre. The VLF mode with $St=0.005$ is also detectable in the intermediate wake and may be associated with a low-frequency radial flapping of the shear layer.